2022
DOI: 10.3390/molecules27134051
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Iron Center Proteins—A Different Class of Hemerythrin-like Proteins

Abstract: Repair of Iron Center proteins (RIC) form a family of di-iron proteins that are widely spread in the microbial world. RICs contain a binuclear nonheme iron site in a four-helix bundle fold, two basic features of hemerythrin-like proteins. In this work, we review the data on microbial RICs including how their genes are regulated and contribute to the survival of pathogenic bacteria. We gathered the currently available biochemical, spectroscopic and structural data on RICs with a particular focus on Escherichia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
(153 reference statements)
0
1
0
Order By: Relevance
“…Similarly, iron, or other metals (such as cadmium), can be bound for storage, detoxification, or function in some other mechanism unrelated to the binding of metals or oxygen ( 49 ). In addition, it has been reported that hemerythrins may play a role in intracellular iron homestatsis, and the repair of iron centers in certain bacteria ( 65 , 66 ). PG_0686 lacks the classic 5 His motif featured in other hemerythrins, and has only one histidine residue predicted to be involved in chloro diiron-oxo binding; as such, it appears to be a part of the group of non-canonical hemerythrin sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, iron, or other metals (such as cadmium), can be bound for storage, detoxification, or function in some other mechanism unrelated to the binding of metals or oxygen ( 49 ). In addition, it has been reported that hemerythrins may play a role in intracellular iron homestatsis, and the repair of iron centers in certain bacteria ( 65 , 66 ). PG_0686 lacks the classic 5 His motif featured in other hemerythrins, and has only one histidine residue predicted to be involved in chloro diiron-oxo binding; as such, it appears to be a part of the group of non-canonical hemerythrin sequences.…”
Section: Discussionmentioning
confidence: 99%